Creating Covid-19 Health Protocol Communication Materials in Filipino: A Translation Study - Alhambra, Claudine; Navarro, Eva (International Journal of Language and Literary Studies, 2021)
Amidst Covid-19, the World Health Organization (WHO) conducted an online course in multiple languages during the first quarter of 2020, as part of their global response to the emergency (Utunen, et al., 2020). Although English is one of the official languages in the Philippines, the country is multilingual, and Filipino is mostly spoken and more widely understood. This translation study aimed to create Covid-19 health protocol communication materials in Filipino to cater to a general audience. Adopting the Interpretive Theory of Translation (ITT) by Danica Seleskovitch and the sixth element (understandable) of the WHO Strategic Communications Framework for Effective Communication (2017), the study developed the Translating and Creating Communications Material Framework to guide the research process. With this, the study was involved in synthesizing gathered information on Covid-19 health protocols which are in the source language, English. The translation itself involved deverbalizing and transcoding, where making sense of the information was done before they were completely translated to the target language, Filipino. Since the main aim is to communicate understandable information, the communication materials are in infographics form. Some English terms were also retained as they are easier to comprehend by the general audience who are households in selected communities.